Acute presentation of port site hernia following robot-assisted hysterectomy: A case report and review of the literature - Rooma Sinha; Rupa Bana; Girija Shankar Mohanty (Wolters Kluwer Medknow Publications, 2021)
Port site hernia (PSH) has been reported following both laparoscopic and robotic surgery. Subsequent surgical intervention increases postoperative morbidity. We report the case of a PSH through the 8-mm trocar following robot-assisted hysterectomy in a 49-year-old female patient, along with a review of the literature. The case was performed with the standard protocol; however, increased intraoperative bleeding was encountered from right uterine artery and vein. Discharged at 48 h, she presented in emergency on the fourth postoperative day with acute intestinal obstruction. Computed tomography scan showed herniation of the jejunal loop through the 8-mm left-sided port. She underwent resection and anastomosis of the necrosed jejunal loop. We review the literature for PSH following robotic gynecological surgeries. Although rare, PSH requires surgical intervention, increasing the postoperative morbidity. Need for fascial closure of 8 mm ports should be considered. High index of suspicion and early recognition can avoid resection of the bowel loop.